Books in Bloom. - Faurot, Kimberly K. (ALA Editions, 2003)
Authors and illustrators spend years developing their creative visions. It is only fitting that their artistic integrity is preserved using beautiful, functional, and creative props for performing the book or poem at story time. What if you could make great props in a reasonable amount of time, learn tips to safely store them, and adapt them for a variety of uses and audiences over the years?. Now you can thoroughly engage your audience in the quality and spirit of your presentation when you use these ''permission granted'' plans, scripts, and props that reflect the original works. Books in Bl.